3D‐Printed Metacarpal Prosthesis in the Treatment of Primary Osteosarcoma of the First Metacarpal: A Novel Surgical Technique - Xuanhong He; Leilei Tian; Chang Zou; Minxun Lu; Zhuangzhuang Li; Guy Romeo Kenmegne; Yitian Wang; Yi Luo; Yong Zhou; Li Min; Chongqi Tu (Orthopaedic Surgery)
ABSTRACT Objective Osteosarcoma at the first metacarpal is extremely rare. Reconstructing the metacarpal after tumor resection is essential, as the thumb accounts for approximately 40%–50% of hand function. Although autografts, arthroplasty, and transposition have been reported as reconstruction options, their use is limited by complications such as secondary injury, nonunion, and displacement. In this study, we present a case of a patient with first metacarpal osteosarcoma who underwent tumor resection followed by reconstruction with a 3D‐printed metacarpal prosthesis. We tend to introduce a novel strategy to reconstruct the first metacarpal and restore the hand function. Methods A 30‐year‐old male with 5‐month history of first metacarpal swelling in the left hand was admitted to our center. Imaging examinations and incision biopsy confirmed a diagnosis of intramedullary well‐differentiated osteosarcoma. A 3D‐printed metacarpal prosthesis was then designed to achieve carpometacarpal (CMC) joint fusion and thumb metacarpophalangeal (MCP) joint reconstruction. Postoperative evaluations included X‐ray and tomosynthesis‐shimadzu metal artifact reduction technology (T‐SMART) imaging to assess bone‐prosthesis integration. Hand function was measured using the Musculoskeletal Tumor Society (MSTS) score and the Disabilities of the Arm, Shoulder, and Hand (DASH) score. Results The tumor was completely resected, and a 3D‐printed metacarpal prosthesis was performed to reconstruct the tumor defect. Postoperative imaging showed that the interface between bone and prosthesis was integrated and that there was no loose, displacement, or fracture of the implant. At the last follow‐up, the patient had an MSTS score of 25/30 and a DASH score of 8/100. The range of motion on thumb MCP joint was 30° of flexion and 0° of extension. The Kapandji thumb opposition score was 4 points. The grip strength was 9 kg (compared to 30 kg on the contralateral side) and the key‐pinch strength was 3 kg (compared to 8 kg on the contralateral side). Conclusion 3D‐printed metacarpal prosthesis could be an effective reconstruction option for patients with low‐grade malignant tumors. Themulti‐planar fixation achieved through 3D surgical planning helps maintain thumb function and restore overall hand function.